Laparoscopic nephron-sparing surgery for complex renal cystic lesions: a single-center experience - Dong, Dexin; Zhang, Yushi (Frontiers in Oncology, 2024)
Objective To explore the feasibility and safety of laparoscopic nephron sparing surgery for complex renal cystic lesions. Methods A retrospective study was conducted on 83 cases of complex renal cystic lesions treated with laparoscopic nephron sparing surgery in our hospital. There were 32 males and 51 females, aged from 24 to 73 years (47.22±9.03 years in average). The diameter of the cysts were 1.5 to 5.9cm (3.44±0.86cm in average). According to Bosniak classification, there were 15 cases of type II, 23 cases of type IIF, 29 cases of type III, and 16 cases of type IV complex renal cystic lesions. According to clinical classification based on the difficulty of laparoscopic partial nephrectomy and the depth of the lesion, the 83 complex renal cystic lesions were divided into 48 cases of extrarenal type, 15 cases of centrally located type, 7 cases of renal sinus type and 13 cases of renal hilum type. Result All 83 patients underwent laparoscopic partial nephrectomy successfully. The surgical time was 35-102 minutes (52.13±14.38 min in average), the intraoperative bleeding volume was 10-200ml (27.25±12.26ml in average), and the renal artery occlusion time was 12-28 minutes (12.46±4.45 min in average). There was no significant change in creatinine before and after surgery. Postoperative pathological results: 71 cases of renal clear cell carcinoma, 5 cases of low-grade malignant potential multilocular cystic renal tumors, and 7 cases of pure renal cysts with all margins negative. Conclusions There is a potential for malignant transformation of complex renal cysts into renal cell carcinoma. For complex renal cysts classified as Bosniak IIF or higher, surgical intervention is recommended, and laparoscopic nephron sparing surgery is safe and effective. The complexity of surgery procedure varies depending on the location classification of the complex renal cysts.